ANALISIS PENGARUH ONLINE CUSTOMER REVIEW DAN CITRA MEREK TERHADAP CONSUMER TRUST DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING (Studi pada Pengguna Tokopedia di Kota Semarang) - Emi Pakpahan; Idris Idris (Diponegoro Journal of Management, 2022)
Online Customer review presents as a liasion between consumers and online product information that can be seen through pictures and descriptiosn provided by other consumers. This reserach aims to develop an empirical research model to overcome the gap between online customer review and consumer trust to create more consumer through purchase decision. This research started with developing a research model to analyse the relations between online customer review, brand image, purchase decision, and consumer trust based on the teory of consumer culture theory and expectation confirmation theory from the previous research. Then, data were collected from 147 respondents using questionnaire consistsing of open and closed questions. The criteria of respondents are user of Tokopedia, residing in Semarang city, and above eighteen years old, and have made at least one purchase on Tokopedia. The data were then analyzed quantitatively and structurally using Structural Equation Modeling (SEM) method using the Analysis Moment of Strcutural (AMOS) program ver.24 as the analysis tool. Result from this research indicates that online customer review give a significant and positive impact towards purchase decision. Brand imaage also positively & significantly impact purchase decision. A significant and positive relation was also found between purchase decision and consumer trust. Hence, all of the hypotheses are accepted. The findings could be taken into consideration by PT Tokopedia to improve consumer’s level of trust and purchase decision.